Phylogenetically related and ecologically similar carnivores harbour similar parasite assemblages. (29th November 2013) - Huang, Shan; Bininda‐Emonds, Olaf R. P.; Stephens, Patrick R.; Gittleman, John L.; Altizer, Sonia; White, Andrew
Summary Most parasites infect multiple hosts, but what factors determine the range of hosts a given parasite can infect? Understanding the broad scale determinants of parasite distributions across host lineages is important for predicting pathogen emergence in new hosts and for estimating pathogen diversity in understudied host species. In this study, we used a new data set on 793 parasite species reported from free‐ranging populations of 64 carnivore species to examine the factors that influence parasite sharing between host species. Our results showed that parasites are more commonly shared between phylogenetically related host species pairs. Additionally, host species with higher similarity in biological traits and greater geographic range overlap were also more likely to share parasite species. Of three measures of phylogenetic relatedness considered here, the number divergence events that separated host species pairs most strongly influenced the likelihood of parasite sharing. We also showed that viruses and helminths tend to infect carnivore hosts within more restricted phylogenetic ranges than expected by chance. Overall, our results underscore the importance of host evolutionary history in determining parasite host range, even when simultaneously considering other factors such as host ecology and geographic distribution.